Molecular-based detection of Ehrlichia spp. in stray dogs-infesting Rhipicephalus ticks in high-altitude of northern Pakistan - Abdul Majid; Muhammad Numan; Hadia Tila; Iram Liaqat; Mohibullah Shah; Zhihua Sun; Abid Ali; Mashal M. Almutairi (PLoS ONE, 2026)
Although ticks are recognized as carriers of zoonotic pathogens, the risks of tick-borne infections associated with dogs have received limited attention. The close interaction between humans and dogs increases the zoonotic potential of pathogens, increasing the urgency of addressing this overlooked vector-borne health risk, especially in developing regions. This study sought to identify tick-borne zoonotic pathogens by collecting ticks from dogs and screening for Ehrlichia species, a group known to pose significant yet often neglected health risks to both humans and animals, particularly in the northern area of Khyber Pakhtunkhwa (KP), Pakistan. Ticks were collected from dogs in the Mardan and Dir Lower districts of Pakistan from June 2024 to May 2025. The collected ticks were morphologically identified and processed for molecular identification using 16S ribosomal DNA (16S rDNA) and cytochrome c oxidase ( cox1 ) sequences for ticks, and 16S rRNA and dsb sequences were used for their associated Ehrlichia spp. Among the 223 dogs observed, 147 were infested with ticks, resulting in an overall prevalence of 66%. Rhipicephalus ticks’ infestation were more common in female dogs (91/113, 80.53%) than in male dogs (56/110, 51%). The occurrence of adult females was highest (173/432, 40%), followed by males (158/432, 36.57%) and nymphs (101/432, 23.37%). Two tick species were identified: Rhipicephalus haemaphysaloides and Rhipicephalus sp., which was identified as a member of the Rhipicephalus sanguineus species complex. This was confirmed by 16S rDNA and cox1 sequences, which showed 99–100% maximum identity. In the phylogenetic trees, Rh. haemaphysaloides clustered with the same species reported from Pakistan, while Rhipicephalus sp. grouped with Rhipicephalus sp. morphotype III from Pakistan and India. Regarding their associated bacterial species, such as Ehrlichia spp., they were detected in both Rhipicephalus sp. and Rh. haemaphysaloides based on 16S rDNA and dsb sequences, which revealed maximum identity with Ehrlichia minasensis and Ehrlichia spp., respectively. These species phylogenetically clustered with the corresponding Ehrlichia species. The high infection rate observed in ticks suggests a significant relationship between companion animals and pathogen vectors. Further studies are necessary to investigate the potential health risks of tick-borne Ehrlichia spp. and their zoonotic implications in the region.